2008
DOI: 10.2519/jospt.2008.2703
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward Responses of Transversus Abdominis Are Directionally Specific and Act Asymmetrically: Implications for Core Stability Theories

Abstract: Therapy, level 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 35 publications
(22 reference statements)
10
67
3
2
Order By: Relevance
“…It is noteworthy that the exercises with arm and leg lift produced asymmetrical activation of the TrA. This finding is consistent with the data by Allison et al, 1 who reported asymmetry of the feedforward TrA activity during an arm-raising task. These data would indicate that the TrA is activated in an asymmetrical manner during asymmetric LSEs, which accounted for 7 of the 11 exercises included in the study.…”
Section: Emg Data Analysissupporting
confidence: 83%
“…It is noteworthy that the exercises with arm and leg lift produced asymmetrical activation of the TrA. This finding is consistent with the data by Allison et al, 1 who reported asymmetry of the feedforward TrA activity during an arm-raising task. These data would indicate that the TrA is activated in an asymmetrical manner during asymmetric LSEs, which accounted for 7 of the 11 exercises included in the study.…”
Section: Emg Data Analysissupporting
confidence: 83%
“…9,27, 55 While there has been considerable debate regarding the contribution of the TrA muscle to control of the lumbar spine and pelvis, 2,3,25,38 it has been argued that the TrA muscle may primarily act via modulation of IAP, fascial tension, and compression of the sacroiliac joints. 9,27,55 Clinical muscle testing of the TrA muscle has been based on its anatomical structure and horizontal fiber arrangement.…”
Section: Methodsmentioning
confidence: 99%
“…40 These findings may represent an attempt by subjects to provide generalized stiffness 12 to the vertebral column or to increase IAP, which can also provide generalized stiffening of the spine. 28,26 While the role of the TrA muscle in control of the spine and pelvis is a topic of recent debate, 2,3,25 there is considerable evidence that the TrA muscle plays an important role in spinal control. 7,26,28,51 There is also evidence that retraining motor control of the deep trunk muscles is commensurate with decreases in LBP and improvements in function in nonathletes.…”
mentioning
confidence: 99%
“…A signal with baseline artifact was not determined as muscle onset, and we identified the onset with continually increased EMG signal from threshold values. 1,2 The time between the onset of the activity of each muscle and the onset of the RA activity was measured as the muscle onset (FIGURE 2).…”
Section: Emg Analysismentioning
confidence: 99%